SENI DAN PENDIDIKAN - Lubis, Nurasiyah Anas (Jurnal Sabilarrasyad, 2021)
Art functions as an educational medium, which provides a series of aesthetic experiences that have a huge impact on children's development, both physically and mentally. Art education in schools can be an effective medium in developing knowledge, skills, creativity, and sensitivity of students. Creativity development can be shaped by play activities. Playing activities that are enjoyed by students can be realized in art education, be it fine arts, dance, music, or drama. The role of Art Education used as a subject in school education is based on the idea that art education is multilingual, multidimensional and multicultural.